3D-printed resonant gold nanocones for out-of-plane terahertz-field-driven electron photoemission - Rovere, Andrea; Piccoli, Riccardo; Bertoncini, Andrea; Jeong, Young Gyun; Payeur, Stéphane; Vidal, François; Kwon, O. Pil; Lee, Seung Heon; Seok, Jin Hong; Morandotti, Roberto; Liberale, Carlo; Razzari, Luca (Optics InfoBase Conference Papers, 2021)
We numerically and experimentally investigate out-of-plane gold nanostructures resonating at terahertz frequencies for field-driven photoemission and compare their performance with a traditional non-resonant nanotip geometry.
Keywords: Electron photoemission; Gold nanostructures; Nanocone; Nonresonant; Out-of-plane; Performance; Terahertz fields; Terahertz frequencies